Reviews of translational medicine and genomics in cardiovascular disease: new disease taxonomy and therapeutic implications cardiomyopathies: therapeutics based on molecular phenotype. - Ashrafian, H; Watkins, H (2007)
The enduring subdivision of cardiomyopathies into hypertrophic (HCM), dilated (DCM), and restrictive (RCM) categories reflects the emphasis of traditional classifications on morphology. Rapid advances in the genetic interrogation of these disorders have redefined their taxonomy and revealed potential conflicts between the old and new classifications. Hypertrophic cardiomyopathy has been redefined as a disease of perturbed sarcomere function. Dilated cardiomyopathy is a disease that results from more varied perturbations, including, but not limited to, defects of the cytoskeleton. Positional cloning and candidate gene approaches have been successful in identifying >40 disease loci, many of which have led to disease genes in HCM, DCM, RCM, and arrhythmogenic right ventricular cardiomyopathy. These findings provide mechanistic insights, permit genetic screening, and to a limited extent, facilitate prognostication. Although single gene analyses rapidly focus down to the underlying mechanistic pathways, they do not take account of all relevant variation in the human genome. Correspondingly, advances in genomics, through microarrays, have facilitated characterization of these broader downstream elements. As well as refining the taxonomic reclassification of cardiomyopathies, these genomic approaches, coupled with functional studies, have identified novel potential therapeutic targets, such as cardiac energetics, calcium handling, and apoptosis. We review the successes and pitfalls of genetic and genomic approaches to cardiomyopathy and their impact on current and future clinical care.